Measuring patent value indicators with patent renewal information - Joo Young Og; Krzysztof Pawelec; Byung-Keun Kim; Rafal Paprocki; EuiSeob Jeong (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper attempts to fill a research gap of literature by constructing the dynamic model into which both ex ante and ex post patent value indicators are incorporated. A patent renewal model is tested using a large set of Pharmaceutical patents granted by the European Patent Office between 1996 and 2009. We test five ex ante indicators and single ex post indicator including family size, patent backward citations, backward references to non-patent literature, number of claims, number of inventors, renewal fee, patent age, application year, and the ex post indicator forward citations. Empirical findings show that three citation related indicators, family size, and the number of claims are positively associated with patent values, while the number of inventors, renewal fee, patent age, and application year are negatively correlated. In addition, forward citations seem to have persistent learning effects on patent values.
Keywords: 650; ex ante indicators; ex post indicators; learning effects; patent renewal model; patent value; pharmaceutical technology field